ANALISIS PENGARUH OUTPUT TERHADAP PENDAPATAN USAHA PELINGGIH UKIRAN BIAS MELELA DI KECAMATAN SUSUT KABUPATEN BANGLI - Pratiwi, Putu Nuria; Sukadana, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2024)
The research objective is the effect of capital, work experience on output and the effect of capital, work experience and output on income and output to mediate the effect of capital and work experience on income in the Bias Melela Carving Pelinggih craft business in Susut District, Bangli Regency. The location of the research is in Susut District, Bangli Regency. The population in this study were craftsmen and entrepreneurs of the Bias Melela Carving Pelinggih craft in Susut District, Bangli Regency with a total of 216 people. Determination of the sample using the Solvin formula. The technique used in taking the number of research samples with the Accidental Sampling method. The methods used in collecting data are observation methods, structured interviews and in-depth interviews. The data analysis technique used consists of Descriptive Analysis, Path Analysis and Sobel Test. The results of the analysis show that: 1) Capital and work experience have a direct positive and significant influence on the output of the Bias Melela Carving Pelinggih Crafts business in Susut District, Bangli Regency. 2) Capital, work experience and output have a positive and significant direct effect on income in the Bias Melela Carving Pelinggih craft business in Susut District, Bangli Regency; 3) Capital and work experience have an indirect effect on income through output in the Bias Melela Carving Pelinggih craft business in Susut District, Bangli Regency. Keywords: Capital, work experience, output , income Klasifikasi JEL: D24,Z22 ,D57,H20,L31